Placental extract suppresses cardiac hypertrophy and fibrosis in an angiotensin II-induced cachexia model in mice. Issue 10 (October 2019) - Yamauchi, Akihiro; Kamiyoshi, Akiko; Sakurai, Takayuki; Miyazaki, Hiroyuki; Hirano, Eiichi; Lim, Hong Seok; Kaku, Taiichi; Shindo, Takayuki
Abstract: Cachexia is an intractable metabolic disorder that causes extreme weight loss. It is a symptom of many chronic diseases, including cancer, liver failure, congestive heart failure and chronic kidney disease, and there is as yet no effective treatment. While the mechanisms underlying cachexia are complex, it is often accompanied by elevated angiotensin II (Ang II). Human placental extract (HPE) is a source of numerous biologically active molecules and has been used clinically to treat chronic hepatitis, liver cirrhosis and other chronic diseases. Here, we investigated the effects of HPE in an Ang II-induced cachexia model in mice. HPE treatment preserved both fat mass and lean body mass and suppressed weight loss in the cachexia model, though food intake was unaffected. Ang II infusion also caused cardiac hypertrophy and fibrosis. HPE suppressed these effects as well as Ang II-induced cardiac expression of genes related to heart failure and cardiac remodeling. HPE also reversed Ang II-induced downregulation of mitochondria-related molecules and suppressed cardiac inflammation and oxidative stress. HPE administration may thus be an effective approach to the treatment of cachexia, cardiac hypertrophy and fibrosis. Abstract : Biochemistry; Cardiac hypertrophy; Human placenta extract; Cardiac fibrosis; Angiotensin II; Cachexia